Perlindungan Hak-Hak Perempuan dalam Perkawinan Campuran Berdasarkan Instrumen-Instrumen Internasional tentang Hak Asasi Manusia - Hikmah, Mutiara (UI Scholars Hub, 2021)
Mixed marriage is common thing in Indonesia. The Data collected by the Civil Register Office said, this type of marriage is increasing from time to time. Mixed marriage, however, has strong relation with women rights concerning nationality aspect. The regulation about women rights are embodied comprehensively, in both national and international human rights instruments. However, the protection of women rights, especially in nationality aspect from the mixed marriage, has not been addressed properly.